Community health workers' attitudes and beliefs toward the elderly - Ferreira, Virgílio Moraes; Ruiz, Tania (Revista de Saúde Pública, 2012)
OBJECTIVE: To describe community health workers' attitudes and beliefs toward the elderly. METHODS: Cross-sectional descriptive study conducted in with 213 community health workers (CHWs) at 12 primary care units and 29 family health centers in the city of Marília, State of São Paulo, Southeastern Brazil, in 2010. Data were collected by means of a sociodemographic questionnaire, a scale of attitudes toward aging (Neri Scale), and a questionnaire to assess gerontological knowledge (the Palmore-Neri-Cachioni Aging Quiz). The Statistical Package for the Social Sciences v. 16.0 was used for data analysis. RESULTS: Community health workers predominantly consisted of young female adults, married, with more than 12 years of schooling and who worked in this activity for over 6 years. Most CHWs reported having experience with elderly people and having elderly people in the family. However, less than half of them received training on the topic of aging. As for attitudes towards the elderly, CHWs stressed both positive aspects such as their wisdom and generosity and negative aspects such as slowness and strictness. They showed low gerontological knowledge, which was directly associated with the training received. Many CHWs stereotyped the elderly as dissatisfied and dependent. CONCLUSIONS: Changing attitudes and improving knowledge on aging are critical for meeting health care demands of elderly people. More appropriate training of CHWs is key for providing adequate primary care to elderly population.